An Integrated Instrument for Measuring Science, Technology, Engineering, and Mathematics: Digital Educational Game Acceptance and Player Experience - Azami, Husna Hafiza R.; Ibrahim, Roslina; Masrom, Suraya; Yusoff, Rasimah Che Mohd; Yaacob, Suraya (International journal of advanced computer science & applications, 2023)
Digital educational games (DEGs) are effective learning tools for subjects related to science, technology, engineering, and mathematics (STEM), yet they are still not widely used among students. Existing instruments typically assess player experience (PX) and acceptance separately, even though both are essential DEG evaluations that can be merged and analyzed concurrently in a thorough manner. This study, therefore, proposes an integrated instrument called DEGAPX that combines fundamental technology acceptance factors with a broad range of PX criteria. The proposed instrument can be used by educators and game designers in the selection and development of DEGs that satisfy the needs of target users. This article describes the process of developing the scale instrument and validating it through two rounds of expert judgment and among students after using three DEGs related to STEM. The proposed instrument, which comprised 15 constructs measured by 67 items, was proven to be reliable and valid.